Silicon-calcium laminated solar cell and preparation method thereof

By adopting a three-layer tunneling structure between the p-i-n type perovskite battery and the silicon battery in perovskite crystalline silicon batteries, the problem of insufficient tunneling junction performance is solved, the recombination efficiency of photogenerated carriers is improved, and the efficiency of solar cells is improved.

CN119584765APending Publication Date: 2025-03-07JIANGSU SHENGKAI NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411876588.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The tunneling performance of existing perovskite crystalline silicon batteries is insufficient, resulting in low radiation recombination efficiency of photogenerated carriers, affecting battery efficiency.

Method used

A p-i-n-type perovskite battery is used as the top battery to build a three-layer tunneling structure with a silicon battery, including an n-type TCO-1 layer, a p-type TCO-2 layer and a metal intermediate layer to improve the tunneling efficiency and recombination rate of electrons and holes.

Benefits of technology

By optimizing the tunneling structure, the carrier transmission efficiency and recombination efficiency are improved, and the overall efficiency of solar cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584765A_ABST
    Figure CN119584765A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-calcium laminated solar cell and a preparation method thereof, the silicon-calcium laminated solar cell comprises a silicon cell serving as a bottom cell and a perovskite cell serving as a top cell, the perovskite cell is a p-i-n type cell, the silicon cell is connected with the perovskite cell through a tunneling structure, and the silicon cell is connected with the perovskite cell through a tunneling structure. The tunneling structure comprises a TCO-1 layer close to the silicon cell, a TCO-2 layer close to the perovskite cell and a middle layer arranged between the TCO-1 layer and the TCO-2 layer, the TCO-1 layer is an n-type TCO, the TCO-2 layer is a p-type TCO, and the middle layer is made of a metal material. The tunneling structure layer of the laminated cell adopts a three-layer structure, so that the cell efficiency is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-calcium stacked solar cell and a preparation method thereof, belonging to the field of solar cells. Background Art

[0002] Among many optoelectronic devices, perovskite solar cells have attracted much attention due to their high photoelectric conversion efficiency and low manufacturing cost. The theoretical efficiency limit of a single-junction perovskite solar cell is about 31%, and the current laboratory record efficiency is 26.7%. According to the calculations of the Photovoltaic Association, for every 1% increase in the absolute value of the efficiency of a photovoltaic cell, its levelized cost of electricity (LCOE) decreases by 5-7%. Therefore, improving the absolute efficiency of the cell is crucial to reducing costs in the photovoltaic industry.

[0003] Tandem cells can break through the efficiency limit of a single junction, and the theoretical efficiency of a two-junction tandem is about 46%. Constructing tandem cells is an effective way to further break through the efficiency and reduce the levelized cost of electricity. Perovskite materials have the advantages of adjustable band gap and solution preparation, which are very suitable for use as top cells in tandem cells. In addition, crystalline silicon cells can be used as bottom cells in tandem cells due to their suitable band gap, mature commercial scale, and excellent stability. Therefore, among the many perovskite tandems, perovskite-crystalline silicon tandems have great commercial prospects. How to effectively use tandem cells to improve the efficiency of solar power generation is the current research focus. Summary of the invention

[0004] In order to improve the performance of the tunnel junction of a perovskite crystalline silicon cell and improve the radiative recombination efficiency of photogenerated carriers, the present invention provides a stacked solar cell, which adopts a pin-type perovskite cell as a top cell and a three-layer structure as a tunneling layer between the crystalline silicon and the perovskite cell, thereby improving the tunneling efficiency and recombination rate of electrons and holes, thereby improving the cell efficiency.

[0005] The technical solution adopted is: a silicon-calcium tandem solar cell, including a silicon cell as a bottom cell and a perovskite cell as a top cell, the perovskite cell is a pin-type cell, the silicon cell and the perovskite cell are connected through a tunneling structure, the tunneling structure includes a TCO-1 layer close to the silicon cell, a TCO-2 layer close to the perovskite cell, and an intermediate layer placed between the TCO-1 layer and the TCO-2 layer, the TCO-1 layer is an n-type TCO, the TCO-2 layer is a p-type TCO, and the intermediate layer is a metal material.

[0006] As a preferred embodiment, the silicon cell is a silicon HJT cell.

[0007] As a preferred embodiment, the thickness of the TCO-1 layer and / or the TCO-2 layer is 2-7 nm, and the material is SnO2, NiO x , indium tin oxide, FTO or a mixture of one or more thereof.

[0008] As a preferred embodiment, the intermediate layer is dispersed metal particles or dispersed metal films or metal clusters.

[0009] As a preferred embodiment, the perovskite battery is stacked with a hole transport layer, a perovskite film layer, an electron transport layer and an electrode layer in sequence from close to the tunneling structure to far away from the tunneling structure, and the perovskite film layer material includes component a and component b, wherein component a is one or a combination of lead iodide, lead bromide, and lead chloride, and component b is one or a combination of cesium iodide, rubidium iodide, formamidine iodine, formamidine bromide, formamidine chloride, methylamine iodine, methylamine bromide, methylamine chloride, cesium chloride, and cesium bromide.

[0010] The present invention also provides a method for preparing a laminated solar cell, comprising the following steps: S01 Obtain silicon cells; S02 Prepare a tunneling structure layer on a silicon cell; S03 Prepare perovskite cells on the tunneling structure layer; The preparation steps of the tunneling structure layer are: A TCO-1 layer is evaporated or atomically layered on the light-absorbing surface of the silicon cell, wherein the TCO-1 layer is an n-type doped TCO; depositing a metal layer on the TCO-1 layer; Vapor depositing or atomic layer depositing a TCO-2 layer on the metal layer, wherein the TCO-2 layer is a p-type doped TCO; The preparation steps of the perovskite battery are: depositing a hole transport layer on the tunneling structure; depositing a perovskite film layer on the hole transport layer; depositing an electron transport layer on the perovskite film layer; An electrode layer is deposited on the electron transport layer.

[0011] As a preferred method, the TCO-1 layer is deposited on the silicon cell by atomic deposition, In2O3 and SnO2 are deposited, the mass ratio of In2O3 to SnO2 is 9:1, the oxygen flow rate during the deposition process is 1sccm~20sccm, and the chamber temperature is 100-300℃; after the deposition is completed, annealing is performed at 100-400℃ to obtain the TCO-1 layer.

[0012] As a preferred method, the TCO-2 layer is formed by atomic deposition, the deposition materials are In2O3, ZnO, and Mg, the oxygen flow rate during the deposition process is 1sccm~20sccm, and the chamber temperature is 100-300℃; after the deposition is completed, annealing is performed at 100-400℃ to obtain the TCO-2 layer.

[0013] As a preferred embodiment, the metal layer is obtained by thermal evaporation of Au, and the metal layer is a discontinuous metal film with a thickness less than 1.2 nm.

[0014] As a preferred method, the preparation method of the perovskite battery is specifically as follows: A The ethanol solution of MeO-2PACz was spin-coated on the ITO glass silicon cell; B Annealing at 100-150 °C to obtain MeO-2PACz hole transport layer.

[0015] C. Component a and component b are mixed and deposited on the hole transport layer by spin coating or scraping coating; component a is one or a combination of lead iodide, lead bromide and lead chloride; component b is one or a combination of cesium iodide, rubidium iodide, formamidine iodine, formamidine bromide, formamidine chloride, methylamine iodine, methylamine bromide, methylamine chloride, cesium chloride and cesium bromide; D. Auxiliary crystallization film formation: After the deposition is completed, the perovskite film is formed into a wet film, and the film formation method is a combination of one or more of vacuum drying, anti-solvent dripping, and air knife curing; E. After the wet film is formed, heating and annealing are performed to evaporate the residual solvent and promote the crystallization of the perovskite film layer to obtain the perovskite film layer; F Atomic layer deposition or evaporation deposition on perovskite film C 60 The material obtains an electron transport layer; G in C 60 A barrier layer SnO2 is deposited on the substrate by atomic layer deposition; H. Prepare the electrode layer on the electron transport layer.

[0016] The beneficial effects of the present invention include: the stacked cell in the present invention uses a pin-type perovskite cell as a top cell and a silicon cell as a bottom cell to form a stacked cell, so that part of the light is absorbed at the perovskite cell, and the remaining light is emitted to the bottom cell to complete the photogenerated carriers, thereby improving the light utilization rate; The present invention sets a tunneling structure layer between the top battery and the bottom battery, and the tunneling structure layer is a three-layer structure. The TCO layers on both sides selectively allow specific carriers to pass through, and the middle layer plays a role in accelerating the carrier recombination rate, thereby improving the carrier transmission efficiency and recombination efficiency; The present invention forms n-type TCO and p-type TCO by selecting doping materials, regulating doping amount, oxygen content, deposition temperature and annealing temperature, thereby selectively transmitting carriers and reducing the non-radiative recombination efficiency of carriers. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Electrical parameters of the batteries obtained in various embodiments and comparative examples; Figure 2 IV curve of the battery obtained in Example 1; Figure 3 IV curve of the battery obtained in Example 2; Figure 4 IV curve of the battery obtained in Example 3; Figure 5 IV curve of the battery obtained in the comparative example. DETAILED DESCRIPTION

[0018] The present invention is described in more specific form below, but it should not be understood that the protection scope of the present invention is limited by the following description. Unless otherwise specified, any scope recorded in the present invention includes any sub-range consisting of the end value and any numerical value between the end values ​​and the end value or any numerical value between the end values. All raw materials of the present invention are not particularly limited to their purity, and the present invention preferably adopts analytical pure. All raw materials of the present invention, their sources and abbreviations all belong to conventional sources and abbreviations in this area, and are all clear and definite in the field of their related uses. Those skilled in the art can purchase them from commercial sources or prepare them by conventional methods according to the abbreviations and corresponding uses.

[0019] "At least one" means one or more, and "more" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the previous and next associated objects are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or plural.

[0020] The silicon-calcium stacked solar cell in the present invention uses a silicon cell as a bottom cell and a perovskite cell as a top cell. The perovskite cell is a pin-type cell. A tunneling structure is provided between the perovskite cell and the silicon cell. The tunneling structure connects the silicon cell and the perovskite cell in series. The tunneling structure needs to have high longitudinal conductivity and high recombination rate, so that the holes generated by the top cell and the electrons generated by the bottom cell recombine at high speed at the tunneling structure, thereby realizing series connection. The tunneling structure includes a three-layer structure, namely, a TCO-1 layer connected to the bottom cell, a TCO-2 layer connected to the top cell, and an intermediate layer, wherein the TCO-1 layer is an n-type TCO (transparent conductive oxide), the purpose of which is to intercept holes on the bottom cell through the n-type TCO, drain electrons, and reduce non-radiative recombination of the bottom cell; the TCO-2 layer is a p-type TCO, the purpose of which is to intercept electrons in the top cell, drain holes in the top cell, and reduce non-radiative recombination of the top cell. The intermediate layer is a metal layer, which plays a role in electrical conduction and accelerating the recombination efficiency of holes and electrons at both ends. The silicon cell may be a perc cell, a topcon cell, or a HJT cell. In order to improve the efficiency of the stacked cell, the silicon cell in the present invention is a HJT cell (heterojunction cell).

[0021] The materials of the TCO-1 layer and the TCO-2 layer in the present invention may be the same or different, and may be selected separately or jointly from SnO2, nickel oxide, indium tin oxide, and FTO (fluorine-doped tin oxide), such as the TCO-1 layer is SnO2, and the TCO-2 layer is SnO2; the TCO-1 layer is SnO2, and the TCO-2 layer is nickel oxide; the TCO-1 layer is SnO2, and the TCO-2 layer is indium tin oxide; the TCO-1 layer is SnO2, and the TCO-2 layer is FTO; the TCO-1 layer is nickel oxide, and the TCO-2 layer is nickel oxide; the TCO-1 layer is nickel oxide, and the TCO-2 layer is indium tin oxide; the TCO-1 layer is nickel oxide, and the TCO-2 layer is FTO; the TCO-1 layer is nickel oxide, and the TCO-2 layer is indium tin oxide; the TCO-2 layer is FTO; the TCO-1 layer is indium tin oxide, and the TCO-2 layer is FTO; the TCO-1 layer is FTO, and the TCO-2 layer is FTO.

[0022] The thickness of the TCO-1 layer and the TCO-2 layer materials can be the same or different, and are selected from 2-10 nm, preferably 2-7 nm, such as 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, and 7 nm. If the thickness is lower than this range, leakage may occur due to the thin film layer, and if the thickness is higher than this range, high lateral conductivity may be formed inside the film layer, resulting in charge leakage.

[0023] The intermediate layer in the present invention is dispersed metal particles or dispersed metal thin films or other forms of metal clusters. The shape of the metal clusters can be any shape. The presence of discontinuous metal clusters is beneficial for the light passing through the top battery to enter the bottom battery through the tunneling structure, and provides catalytic sites for the recombination of carriers. For ease of preparation, a discontinuous metal thin film sheet can be formed on TCO-1 by magnetron or atomic deposition, with a thickness of less than 1nm.

[0024] The perovskite battery of the present invention comprises a hole transport layer, a perovskite film layer, an electron transport layer and an electrode layer which are arranged in sequence, wherein the perovskite film layer material comprises component a and component b, component a is one or a combination of lead iodide, lead bromide and lead chloride, and component b is one or a combination of cesium iodide, rubidium iodide, formamidine iodine, formamidine bromide, formamidine chloride, methylamine iodine, methylamine bromide, methylamine chloride, cesium chloride and cesium bromide.

[0025] The method for preparing the stacked battery comprises the following steps: S01 Obtain silicon cells; S02 Prepare a tunneling structure layer on a silicon cell; S03 Prepare perovskite cells on the tunneling structure layer; The preparation method of the tunneling structure layer is as follows: (1) depositing a TCO-1 layer on the light-absorbing surface of the silicon cell. The deposition method can be vacuum evaporation or ALD (atomic layer deposition). Taking ALD as an example, the specific method is as follows: depositing In2O3 and SnO2 on the silicon cell. The mass ratio of In2O3 to SnO2 is 9:1. The oxygen flow rate during the deposition process is 1sccm to 20sccm. Controlling the partial pressure of oxygen is an important factor in achieving n-type conductivity. Usually, the ITO layer is deposited under low oxygen conditions to increase oxygen vacancies and thus enhance the electron concentration. The chamber temperature is 100-300°C. At this temperature, it can promote the improvement of crystal quality and the effective integration of dopants, while reducing the formation of other adverse defects. After the deposition is completed, annealing is performed at 100-400°C to obtain the TCO-1 layer. Doping Sn in ITO is beneficial to increase the carrier concentration, making it more significantly exhibit n-type characteristics.

[0026] (2) Deposit a metal layer on the TCO-1 layer. The metal material can be silver, aluminum, gold, etc. Taking gold as an example, 1nm thick Au clusters are deposited by thermal evaporation. The discontinuous gold film layer can avoid the metal film layer blocking light and affecting performance. The gold clusters formed by thermal evaporation can obtain a suitable lateral density and can form effective recombination centers without blocking the incident light.

[0027] (3) Depositing TCO-2 on the metal layer by atomic layer deposition, wherein the deposition materials are In2O3 and ZnO2 in a ratio of 1:9 or 2:8. During the deposition process, the oxygen flow rate is 1 sccm to 20 sccm, and the chamber temperature is 100-300°C; after the deposition is completed, annealing is performed at 100-400°C to obtain the TCO-2 layer. The addition of metal Ag can replace the position of indium or zinc in the oxide and increase the carrier concentration.

[0028] Adjusting the oxygen partial pressure is beneficial to forming oxygen vacancies in the TCO material layer, thereby changing the conductive properties. The crystallinity, conductivity, oxygen content, oxygen defects, etc. of the film can be adjusted by adjusting the annealing temperature and the annealing atmosphere. Therefore, in the process of depositing TCO-1 and TCO-2, the present invention obtains a material layer with desired conductive properties by adjusting the oxygen flow rate, chamber temperature and annealing temperature.

[0029] The following is further described with specific examples. Example

[0030] The preparation method of the stacked battery in this embodiment is: S01 Get the base Using HJT battery as the substrate, it was first ultrasonically cleaned in detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0031] S02 Preparation of tunneling structure layer (1) TCO-1 is obtained by depositing ITO (indium tin oxide). In this embodiment, the ratio of indium (In) and tin (Sn) is adjusted during the deposition process so that the deposition mass ratio of In2O3 to SnO2 is 9:1, the oxygen partial pressure is adjusted so that the oxygen flow rate is 5 sccm, and the chamber temperature is adjusted to 150°C. After depositing a 5 nm thick film layer, the deposition is completed.

[0032] After annealing in oxygen or nitrogen, the oxygen vacancy concentration and distribution of the material are adjusted to optimize its conductivity, and the annealing temperature is 200° C. The obtained TCO-1 film layer shows excellent n-type doping characteristics.

[0033] (2) Then, 1 nm thick Au is deposited by thermal evaporation. The Au deposited in this way exists in the form of clusters, that is, a discontinuous island-like metal film. The Au clusters provide catalytic sites for the recombination of carriers and accelerate carrier transport.

[0034] (3) Continue to deposit IZO (indium zinc oxide) to obtain TCO-2. The deposited materials are In2O3, ZnO, and Mg. The mass ratio of In2O3, ZnO, and Mg is 10:90:0.8. The addition of Mg is beneficial to replace certain positions in the IZO oxide, thereby increasing the carrier concentration. The oxygen partial pressure is adjusted to make the oxygen flow rate 15sccm, and the chamber temperature is adjusted to 200°C. After depositing a 5nm thick film layer, the deposition is completed.

[0035] After annealing in oxygen or nitrogen, the oxygen vacancy concentration and distribution of the material are adjusted to optimize its conductivity. The annealing temperature is 300° C. The obtained TCO-2 film layer shows excellent p-type doping characteristics.

[0036] S03 Preparation of hole layer (1) Mix 1 mg of MeO-2PACz with 1 mL of ethanol solution to obtain a 1 mg / mL MeO-2PACz solution, filter it with a 0.45 μm filter element to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution onto the tunneling structure layer at a rate of 3300 rpm for 30 s. (3) Annealing at 120°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 3 nm.

[0037] Preparation of S04 perovskite film (1) Preparation of FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Solution: The concentration of the solution is 1.7M, and the molar ratio of FAI, MABr, CsI, PbI2, and PbBr2 is 0.8:0.15:0.05:0.7:0.3. The solvent is a mixed solution of DMF and DMSO, with a volume ratio of 5:1. Heat at 70°C and stir for 2 hours until completely dissolved. Use a 0.45μm filter to filter out larger particles in the solution to obtain FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Precursor solution.

[0038] (2) Place the prepared FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25)3 The precursor solution was spin-coated on the hole transport layer at a spin-coating rate of 3000 rpm for 30 seconds. At the 10th second of spin-coating, 150 μL of anti-solvent toluene was evenly added to the film layer, followed by annealing at 100°C for 30 minutes under a nitrogen atmosphere, and then cooled for use to form a perovskite film layer with a thickness of 600 nm.

[0039] Preparation of S05 electron transport layer (1) Use vacuum evaporation equipment to evaporate C by thermal evaporation 60 Materials, a 20nm electron transport layer is formed on the perovskite film layer, and the evaporation vacuum degree is below 7*10-4Pa.

[0040] Preparation of S06 hole blocking layer: (2) Using vacuum evaporation equipment and ALD method, 60 A 10nm barrier layer of SnO2 is deposited on top.

[0041] Preparation of S07 electrode A 100nm copper (Cu) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0042] A stacked battery was prepared.

[0043] Comparative Example 1 The only difference from Example 1 is that the tunneling structure layer is a single-layer structure. The preparation method is: S01 Get the base Using HJT battery as the substrate, it was first ultrasonically cleaned in detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0044] S02 Preparation of tunneling structure layer TCO was obtained by depositing ITO, with a deposition mass ratio of In2O3 to SnO2 of 9:1. The oxygen partial pressure was adjusted to make the oxygen flow rate 5 sccm. The chamber temperature was adjusted to 150°C. After depositing a 5 nm thick film layer, the deposition was completed.

[0045] S03 Preparation of hole layer (1) Mix 1 mg of MeO-PACz with 1 mL of ethanol solution to obtain a 1 mg / mL MeO-2PACz solution, filter it with a 0.45 μm filter to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution onto the tunneling structure layer at a rate of 3300 rpm for 30 s. (3) Annealing at 120°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 3 nm.

[0046] Preparation of S04 perovskite film (1) Preparation of FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Solution: The concentration of the solution is 1.7M, and the molar ratio of FAI, MABr, CsI, PbI2, and PbBr2 is 0.8:0.15:0.05:0.7:0.3. The solvent is a mixed solution of DMF and DMSO, with a volume ratio of 5:1. Heat at 70°C and stir for 2 hours until completely dissolved. Use a 0.45μm filter to filter out larger particles in the solution to obtain FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Precursor solution.

[0047] (2) Place the prepared FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 The precursor solution was spin-coated on the hole transport layer at a spin-coating rate of 3000 rpm for 30 seconds. At the 10th second of spin-coating, 150 μL of anti-solvent toluene was evenly added to the film layer, followed by annealing at 100°C for 30 minutes under a nitrogen atmosphere, and then cooled for use to form a perovskite film layer with a thickness of 600 nm.

[0048] Preparation of S05 electron transport layer (1) Use vacuum evaporation equipment to evaporate C by thermal evaporation 60 Materials, a 20nm thick electron transport layer is formed on the perovskite film layer, and the evaporation vacuum degree is below 7*10-4Pa.

[0049] Preparation of S06 hole blocking layer: (2) Using vacuum evaporation equipment and ALD method, 60 A 10nm barrier layer of SnO2 is deposited on top.

[0050] Preparation of S07 electrode A 100nm copper (Cu) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0051] A stacked battery was prepared.

[0052] Example 2 The preparation method of the stacked battery in this embodiment is: S01 Get the base Using HJT battery as the substrate, it was first ultrasonically cleaned in detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0053] S02 Preparation of tunneling structure layer (1) TCO-1 was obtained by depositing ITO. In this embodiment, the ratio of indium (In) and tin (Sn) was adjusted during the deposition process so that the deposition mass ratio of In2O3 to SnO2 was 8.5:1.5, the oxygen partial pressure was adjusted so that the oxygen flow rate was 7.5 sccm, and the chamber temperature was adjusted to 150°C. After a 5 nm thick film layer was deposited, the deposition was completed.

[0054] After annealing in oxygen or nitrogen, the oxygen vacancy concentration and distribution of the material are adjusted to optimize its conductivity. The annealing temperature is 220° C. The obtained TCO-1 film layer shows excellent n-type doping characteristics.

[0055] (2) Then, 0.8 nm of Ag was deposited by thermal evaporation. The Ag deposited in this way existed in the form of clusters, i.e., a discontinuous island-like metal film. The Ag clusters provided catalytic sites for the recombination of carriers, thus accelerating the carrier transport.

[0056] (3) Continue to deposit IZO to obtain TCO-2. The deposited materials are In2O3, ZnO, and Cu, and the material mass ratio is In2O3:ZnO:Cu=20:80:1. The addition of Cu is beneficial to replace certain positions in the IZO oxide, thereby increasing the carrier concentration. The oxygen partial pressure is adjusted to make the oxygen flow rate 15sccm, and the chamber temperature is adjusted to 200℃. After depositing a 5nm thick film layer, the deposition is completed.

[0057] After annealing in oxygen or nitrogen, the oxygen vacancy concentration and distribution of the material are adjusted to optimize its conductivity. The annealing temperature is 300° C. The obtained TCO-2 film layer shows excellent p-type doping characteristics.

[0058] S03 Preparation of hole layer (1) Mix 1 mg of MeO-PACz with 1 mL of ethanol solution to obtain a 1 mg / mL MeO-2PACz solution, filter it with a 0.45 μm filter to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution onto the tunneling structure layer at a rate of 3300 rpm for 30 s. (3) Annealing at 120°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 3 nm.

[0059] Preparation of S04 perovskite film (1) Preparation of FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Solution: The concentration of the solution is 1.7M, and the molar ratio of FAI, MABr, CsI, PbI2, and PbBr2 is 0.8:0.15:0.05:0.7:0.3. The solvent is a mixed solution of DMF and DMSO, with a volume ratio of 5:1. Heat at 70°C and stir for 2 hours until completely dissolved. Use a 0.45μm filter to filter out larger particles in the solution to obtain FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Precursor solution.

[0060] (2) Place the prepared FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 The precursor solution was spin-coated on the hole transport layer at a spin-coating rate of 3000 rpm for 30 seconds. At the 10th second of spin-coating, 150 μL of anti-solvent toluene was evenly added to the film layer, followed by annealing at 100°C for 30 minutes under a nitrogen atmosphere, and then cooled for use to form a perovskite film layer with a thickness of 600 nm.

[0061] Preparation of S05 electron transport layer (1) Use vacuum evaporation equipment to evaporate C by thermal evaporation 60 Materials, forming a 20nm thick electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.

[0062] Preparation of S06 hole blocking layer: (2) Using vacuum evaporation equipment, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material is evaporated by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum is 7*10 -4 Below Pa.

[0063] Preparation of S07 electrode A 100nm copper (Cu) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0064] A stacked battery was prepared.

[0065] Example 3 The preparation method of the stacked battery in this embodiment is: S01 Get the base Using HJT battery as the substrate, it was first ultrasonically cleaned in detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0066] S02 Preparation of tunneling structure layer (1) TCO-1 was obtained by depositing ITO. In this embodiment, the ratio of indium (In) and tin (Sn) was adjusted during the deposition process so that the deposition mass ratio of In2O3 to SnO2 was 8.8:1.2, the oxygen partial pressure was adjusted so that the oxygen flow rate was 9 sccm, and the chamber temperature was adjusted to 170°C. After a 7 nm thick film layer was deposited, the deposition was completed.

[0067] After annealing in oxygen or nitrogen, the oxygen vacancy concentration and distribution of the material are adjusted to optimize its conductivity, and the annealing temperature is 200° C. The obtained TCO-1 film layer shows excellent n-type doping characteristics.

[0068] (2) Subsequently, 0.8 nm thick Al was deposited by thermal evaporation. The Al deposited in this way existed in the form of clusters, i.e., a discontinuous island-like metal film. The Al clusters provided catalytic sites for the recombination of carriers, thus accelerating the carrier transport.

[0069] (3) Continue to deposit IZO to obtain TCO-2. The deposited materials are In2O3, ZnO2, and Ga, and the material mass ratio is 10:90:1.1. The addition of Ga is beneficial to replace certain positions in the IZO oxide, thereby increasing the carrier concentration. The oxygen partial pressure is adjusted to make the oxygen flow rate 15sccm, and the chamber temperature is adjusted to 200℃. After depositing a 5nm thick film layer, the deposition is completed.

[0070] After annealing in oxygen or nitrogen, the oxygen vacancy concentration and distribution of the material are adjusted to optimize its conductivity. The annealing temperature is 300° C. The obtained TCO-2 film layer shows excellent p-type doping characteristics.

[0071] S03 Preparation of hole layer (1) Mix 1 mg of MeO-PACz with 1 mL of ethanol solution to obtain a 1 mg / mL MeO-2PACz solution, filter it with a 0.45 μm filter to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution onto the tunneling structure layer at a rate of 3300 rpm for 30 s. (3) Annealing at 120°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 3 nm.

[0072] Preparation of S04 perovskite film (1) Preparation of FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Solution: The concentration of the solution is 1.7M, and the molar ratio of FAI, MABr, CsI, PbI2, and PbBr2 is 0.8:0.15:0.05:0.7:0.3. The solvent is a mixed solution of DMF and DMSO, with a volume ratio of 5:1. Heat at 70°C and stir for 2 hours until completely dissolved. Use a 0.45μm filter to filter out larger particles in the solution to obtain FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 Precursor solution.

[0073] (2) Place the prepared FA 0.85 MA 0.10 Cs 0.05 Pb(I 0.75 Br 0.25 )3 The precursor solution was spin-coated on the hole transport layer at a spin-coating rate of 3000 rpm for 30 seconds. At the 10th second of spin-coating, 150 μL of anti-solvent toluene was evenly added to the film layer, followed by annealing at 100°C for 30 minutes under a nitrogen atmosphere, and then cooled for use to form a perovskite film layer with a thickness of 600 nm.

[0074] Preparation of S05 electron transport layer (1) Using vacuum evaporation equipment, C60 material is evaporated by thermal evaporation to form a 20nm electron transport layer on the perovskite film layer. The evaporation vacuum degree is 7*10 -4 Below Pa.

[0075] Preparation of S06 hole blocking layer: (2) Using vacuum evaporation equipment, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material is evaporated by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum degree is below 7*10-4Pa.

[0076] Preparation of S07 electrode A 100nm copper (Cu) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0077] A stacked battery was prepared.

[0078] The electrical properties of the laminated batteries obtained in the above embodiments and comparative examples were tested, and the data are shown in Table 1. Figure 1-3 As shown, it can be seen that the difference between Example 1 and the comparative example is only the tunneling structure. The stacked battery in Example 1 is significantly better than the battery obtained in the comparative example in terms of open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF), and photoelectric conversion efficiency (PCE), indicating that the three-layer tunneling structure in the present invention has a positive effect on the electrical performance of the battery and improves the photoelectric conversion efficiency. The test data corresponding to Examples 1 to 3 show that the three-layer tunneling structure in the present invention can obtain an open circuit voltage of more than 1.7V and a photoelectric conversion efficiency of more than 21% in various types of pin perovskite and crystalline silicon stacked batteries.

[0079] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A calcium-silicon tandem solar cell, characterized in that: It includes a silicon cell as a bottom cell and a perovskite cell as a top cell, wherein the perovskite cell is a pin-type cell, and the silicon cell and the perovskite cell are connected via a tunneling structure, wherein the tunneling structure includes a TCO-1 layer close to the silicon cell, a TCO-2 layer close to the perovskite cell, and an intermediate layer disposed between the TCO-1 layer and the TCO-2 layer, wherein the TCO-1 layer is an n-type TCO, the TCO-2 layer is a p-type TCO, and the intermediate layer is a metal material.

2. The tandem solar cell according to claim 1, characterized in that: The silicon cell is a silicon HJT cell.

3. The calcium-silicon tandem solar cell according to claim 1, characterized in that: The thickness of the TCO-1 layer and / or the TCO-2 layer is 2-7 nm, and the material is SnO2, NiO x , indium tin oxide, FTO, or a mixture of two or more thereof.

4. The calcium-silicon tandem solar cell according to claim 1, characterized in that: The intermediate layer is dispersed metal particles or dispersed metal films or metal clusters.

5. The silicon-calcium tandem solar cell according to claim 1, characterized in that: The perovskite battery is stacked with a hole transport layer, a perovskite film layer, an electron transport layer and an electrode layer in sequence from close to the tunneling structure to far away from the tunneling structure. The perovskite film layer material includes component a and component b. Component a is one or a combination of lead iodide, lead bromide and lead chloride. Component b is one or a combination of cesium iodide, rubidium iodide, formamidine iodine, formamidine bromide, formamidine chloride, methylamine iodine, methylamine bromide, methylamine chloride, cesium chloride and cesium bromide.

6. A method for preparing a silicon-calcium laminated solar cell, characterized in that: The following steps are included S01 Obtain silicon cells; S02 Prepare a tunneling structure layer on a silicon cell; S03 Prepare perovskite cells on the tunneling structure layer; The preparation steps of the tunneling structure layer are: A TCO-1 layer is deposited by evaporation, sputtering or atomic layer deposition on the light-absorbing surface of the silicon cell, wherein the TCO-1 layer is an n-type doped TCO; depositing a metal layer on the TCO-1 layer; Vapor depositing, sputtering or atomic layer deposition of a TCO-2 layer on the metal layer, wherein the TCO-2 layer is a p-type doped TCO; The preparation steps of the perovskite battery include: depositing a hole transport layer on the tunneling structure; Depositing a perovskite film layer; depositing an electron transport layer; Deposition of electrode layers.

7. The preparation method according to claim 6, characterized in that: The TCO-1 layer is deposited on the silicon cell by atomic layer deposition, and In2O3 and SnO2 are deposited. The mass ratio of In2O3 to SnO2 is 9:

1. The oxygen flow rate during the deposition process is 1sccm to 20sccm, and the chamber temperature is 100-300°C. After the deposition is completed, annealing is performed at 100-400°C to obtain the TCO-1 layer.

8. The preparation method according to claim 6, characterized in that: The TCO-2 layer is formed by atomic deposition, and the deposition materials are In2O3, ZnO, and Mg. During the deposition process, the oxygen flow rate is 1sccm to 20sccm, and the chamber temperature is 100-300°C. After the deposition is completed, annealing is performed at 100-400°C to obtain the TCO-2 layer.

9. The preparation method according to claim 6, characterized in that: The metal layer is obtained by thermal evaporation of Au and / or Ag, and the metal layer is a discontinuous metal film with a thickness less than 1.2 nm.

10. The preparation method according to claim 6, characterized in that: The preparation method of the perovskite battery is specifically as follows: A. Spin-coat the ethanol solution of MeO-2PACz on the tunneling structure layer of the silicon cell; B. Annealing at 100-150°C to obtain a MeO-2PACz hole transport layer; C. Component a and component b are mixed and deposited on the hole transport layer by spin coating or scraping coating; component a is one or a combination of lead iodide, lead bromide and lead chloride; component b is one or a combination of cesium iodide, rubidium iodide, formamidine iodine, formamidine bromide, formamidine chloride, methylamine iodine, methylamine bromide, methylamine chloride, cesium chloride and cesium bromide; D. Auxiliary crystallization film formation: After the deposition is completed, the perovskite film is formed into a wet film, and the film formation method is a combination of one or more of vacuum drying, anti-solvent dripping, and air knife curing; E. After the wet film is formed, heating and annealing are performed to evaporate the residual solvent and promote the crystallization of the perovskite film layer to obtain the perovskite film layer; F Atomic layer deposition or evaporation deposition on perovskite film C 60 The material obtains an electron transport layer; G in C 60 A barrier layer SnO2 is deposited on the substrate by atomic layer deposition; H Preparation of electrode layer.

Citation Information

Cited By

  • Perovskite crystalline silicon laminated cell and preparation method and application thereof

    CN121665830A

  • Perovskite crystalline silicon tandem cell and preparation method and application thereof

    CN121665830B